Internalization of Tolerance Value: Strategies and Innovations of Islamic Religious Education Teachers in Senior High Schools - Abdul Muid (Tafkir: Interdisciplinary Journal of Islamic Education, 2022)
This article aims to describe the importance of improving tolerance values in senior high schools. What is the Islamic Religious Education Teacher's Strategy for fostering Tolerance Character? The research method that has been used is qualitative with a case study approach. The choice of research place is based on the fact that Daruttaqwa Gresik High School is a multicultural-based school that accepts students from various aspects. Data analysis techniques by following the Huberman model. The findings of this study are The initial step in fostering tolerance values at Daruttaqwa Gresik High School involves careful planning from PAI teachers. This planning includes developing teaching strategies and combining methods and techniques that are tailored to educational goals. In addition, this planning also includes preparing learning materials, gathering educational resources, and designing evaluations to measure students' understanding of the subject matter. The culmination of these efforts results in a comprehensive lesson plan.